(untitled) (International Journal of Food and Nutritional Sciences, 2024)
“Life presents a continuous chain of struggle for existence survival” (524), cites S.K. Mangal from Darwin’s statement. The psyche, often known as the human mind, spirit, or mind, plays a significant role in determining our behavioral characteristics. For individuals who hold the belief that people are flawed, it is important to recognize that this state of brokenness does not occur spontaneously. However, it commences by delving into the past, namely focusing on our familial connections. When the mind is impacted, cognitive abilities become difficult, and individuals will undergo personality alterations. Surveys conducted in advanced industrialized countries suggest that there is no certain life stage that brings significantly more happiness or complete fulfillment compared to persons who have attained remarkable accomplishments.